Knowledge, attitude and practice study of HIV in female adolescents presenting for contraceptive services in a rural health district in the north-east of Namibia - Alexis Ntumba; Vera Scott; Ehimario Igumbor (African Journal of Primary Health Care & Family Medicine, 2012)
Background: Namibia bears a large burden of Human Immunodeficiency Virus (HIV), and the youth are disproportionately affected.Objectives: To explore the current knowledge, attitudes and behaviour of female adolescents attending family planning to HIV prevention.Methods: A cross-sectional study design was used on a sample 251 unmarried female adolescents aged from 13 years to 19 years accessing primary care services for contraception using an interviewer- administered questionnaire. Data were analysed using Epi Info 2002.Crude associations were assessed using cross-tabulations of knowledge, attitude and behaviour scores against demographic variables. Chi-square tests and odds ratios were used to assess associations from the cross-tabulations. All p-values < 0.05 were considered statisticallysignificant.Results: A quarter of sexually active teenagers attending the family-planning services did not have adequate knowledge of HIV prevention strategies. Less than a quarter (23.9%) always used a condom. Most respondents (83.3%) started sexual intercourse when older than 16 years, but only 38.6% used a condom at their sexual debut. The older the girls were at sexual debut, the more likely they were to use a condom for the event (8% did so at age 13 years and 100% atage 19 years).Conclusions: Knowledge of condom use as an HIV prevention strategy did not translate into consistent condom use. One alternate approach in family-planning facilities may be to encourage condom use as a dual protection method. Delayed onset of sexual activity and consistent use of condoms should be encouraged amongst schoolchildren, in the school setting.